Behavioral problems associated with an adolescent's ADHD symptoms and the family role as a possible protective factor - Stefán Þorri Helgason 1991- (2020)
The purpose of this study was to examine if parental support and parental control served as protective factors against violent behavior associated with adolescent's ADHD symptoms. Studies have shown that parenting style can play a fundamental role in reducing disturbing behavior that has been repeatedly linked with ADHD. However, there appears to be a lack of information on which factors in the parental style matters most in reducing the disruptive behavior associated with ADHD. Data from the survey Youth in Iceland 2014, were applied for the analysis in this study. The sample was regarded as a representative and consisted of 2143 participants assembled randomly from all elementary schools in Iceland in eighth, ninth, tenth grade, 1045 males (48.8%), and 1083 females (50.5%). A Binary logistic regression was applied to test for the main effects of parental support and parental control when predicting violent behavior as well the interaction effects between ADHD and parental support and parental control when predicting violent behavior for males and females. The results revealed that ADHD symptoms were significantly related to a higher risk of violent behavior for both females and males. However, parental control was significantly related to a lower risk of violent behavior for females only when controlling for other variables. Finally, the interaction effect between ADHD and parental control when predicting violent behavior was statistically significant for males only, indicating that parental control could function as a buffer in the relationship between ADHD symptoms and violent behavior for males. Markmið rannsóknarinnar var að kanna hvort að stuðningur foreldra og yfirsýn foreldra gætu virkað sem verndandi þættir gegn truflandi hegðun unglinga með ADHD einkenni. Rannsóknir hafa sýnt að foreldrastíll geti spilað mikilvægt hlutverk í því að minnka tíðni á áhættuhegðun sem ítrekað hefur verið tengt við ADHD. Það virðist þó vera skortur á rannsóknum sem hafa skoðað hvaða þættir það eru innan ...